A randomised controlled trial of the Home Independence Program, an Australian restorative home‐care programme for older adults. (25th September 2012) - Lewin, Gill; De San Miguel, Kristen; Knuiman, Matthew; Alan, Janine; Boldy, Duncan; Hendrie, Delia; Vandermeulen, Suzanne
Abstract A randomised controlled trial was conducted to test the effectiveness of the Home Independence Program (HIP), a restorative home‐care programme for older adults, in reducing the need for ongoing services. Between June 2005 and August 2007, 750 older adults referred to a home‐care service for assistance with their personal care participated in the study and received HIP or 'usual' home‐care services. Service outcomes were compared at 3 and 12 months. Subgroups of 150 from each group were also compared on functional and quality of life measures. Data were analysed by 'intention‐to‐treat' and 'as‐treated'. The intention‐to‐treat analysis showed at 3 and 12 months that the HIP group was significantly less likely to need ongoing personal care [Odds ratio (OR) = 0.18, 95% CI = 0.13–0.26, P < 0.001; OR = 0.22, 95% CI = 0.15–0.32, P < 0.001]. Both subgroups showed improvements on the individual outcome measures over time with the only significant differences being found at 12 months for Instrumental Activities of Daily Living (IADL) in the as‐treated analysis. Contamination of the control group by an increased emphasis on independence across the home‐care agency involved, together with other methodological problems encountered, is thought to account for the few differences between groups in individual outcomes. Despite no difference between the groups over time in their overall ADL scores, a significantly smaller proportion of the HIP group required assistance with bathing/showering, the most common reason for referral, at 3 and 12 months. The results support earlier findings that participating in a short‐term restorative programme appears to reduce the need for ongoing home care. The implementation of such programmes more broadly throughout Australia could substantially offset the projected increase in demand for home care associated with the five‐fold projected increase in numbers of the oldest old expected over the next 40 years.